Performance of the CMS muon trigger system in proton-proton collisions at √ 𝒔 = 13 TeV; Journal of Instrumentation; Vol. 16, iss. 7 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2021, 2021)
Title screen